THE EFFECT OF CHEMICAL AND BIOLOGICAL TREATMENTS ON IMPROVING THE NUTRITIVE VALUE OF CORN COBS AND WILD REED (Baghdad Science Journal, 2007)
This study was conducted in Animal Resources Department , College of Agriculture to estimate the effect of chemical and biological treatments to improve the nutritive value of poor quality roughages ( corn cobs and wild reed ) .The feeds were treated chemically with 4% NaoH solution ,whereas Aspergillus niger was used to ferment corn cobs and wild reed samples .The chemical analysis showed that protein percentages of corn cobs and wild reed was increased significantly (P